2020
DOI: 10.18343/jipi.25.3.388
|View full text |Cite
|
Sign up to set email alerts
|

Potensi dan Karakterisasi Fisiologis Bakteri Endofit Asal Tanaman Kakao Sehat sebagai Pemacu Pertumbuhan Benih Kakao

Abstract: This study aimed to obtain endophytic bacterial isolates originated from healthy cacao plant, potential for plant-growth promoting of cacao seedlings. This study was carried out in the Phytopathology Laboratory Unit of the Plant Protection Department, Faculty of Agriculture, Halu Oleo University. This study was conducted using a completely randomized design (CRD) using ten isolates of endophytic bacteria from healthy cocoa plants as treatments, plus a control treatment. The experiment was conducted in a screen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
(12 reference statements)
0
3
0
Order By: Relevance
“…Effect of endophite bacteria on length of rice plant canopy showed that almost all isolates tested were able to stimulate the growth of rice plant canopy compared to control (Munif et al, 2016). In research (Khaeruni et al, 2020) treatment of endophite bacterial isolates significantly affected height of cocoa plants and was significantly different compared to controls. Arabidopsis plants treated with Bacillus aryabhattai showed increased growth compared to control plants.…”
Section: Plant Height (Cm)mentioning
confidence: 88%
“…Effect of endophite bacteria on length of rice plant canopy showed that almost all isolates tested were able to stimulate the growth of rice plant canopy compared to control (Munif et al, 2016). In research (Khaeruni et al, 2020) treatment of endophite bacterial isolates significantly affected height of cocoa plants and was significantly different compared to controls. Arabidopsis plants treated with Bacillus aryabhattai showed increased growth compared to control plants.…”
Section: Plant Height (Cm)mentioning
confidence: 88%
“…From these results, endophytic bacteria are able to provide effectiveness against rubber plant, this is in line with research (Munif et al, 2016) The effect of endophite bacteria on the length of the rice plant canopy showed that almost all the isolates tested were able to stimulate the growth of the rice plant canopy compared to the control. In research (Khaeruni et al, 2020) the treatment of endophite bacterial isolates significantly affected the height of the cocoa plants and was significantly different compared to the controls. Arabidopsis plants treated with B. aryabhattai showed increased growth compared to control plants.…”
Section: Plant Heightmentioning
confidence: 93%
“…Based on results test there are 5 isolation of bacteria derived from roots and stems of cocoa plants, produced auxin hormones. Previous researchers have proven that physiological improvement of plant seeds and plant growth retardation by addition of endophytic bacteria or other microbial groups were related to the ability of microbes to increase nitrogen fixation, auxin production, and phosphate dissolving ability as per research (Khaeruni et al, 2020). Ability of microbes produced auxin was also influenced by type of microorganism species.…”
Section: Test Potential Of Endophytic Bacteria Of Cocoa Plants In Pro...mentioning
confidence: 97%